Green 5G ultra-dense wireless heterogeneous networks:guidelines,techniques,and challenges - Yuzhou LI; Tao JIANG; Yang CAO; Zan LI (Dianxin kexue)
Ultra-dense wireless heterogeneous network (Ud-HetNet) has been recognized as one of the most promising 5G network-organization techniques to significantly improve the wireless capacity and thus solve the 1 000× data challenge faced by cellular networks.However,counter to the expected 5G vision,although benefiting from the spectrum efficiency (SE) improvement,ultra-dense network deployment significantly increases system energy consumption and thus decreases network energy efficiency (EE).The key theories and techniques for energy-efficiently deploying Ud-HetNet were investigated from two aspects of macroscopic network matching and microscopic resource aggregation by exploiting their overall network management capabilities and network diversity effects.Specifically,the overall design guidelines for green evolution were introduced firstly,and then three techniques,namely load-aware base station on/off switching,proactive caching,and interference-aware cross-network resource allocation,were proposed to improve the network EE.Open issues and challenges that need to be further explored were also discussed.